Playing Out Transformative Adaptation in CCAFS Benchmark Sites in East Africa: "When, Where, How and With Whom?" - Läderach, Peter R.D.; Eitzinger, Anton; Twyman, Jennifer; Shikuku, Kelvin Mashisia (2014)
As part of this CCAFS project we collected various types of data in order to better understand vulnerabilities of smallholder farmers in East Africa to climate change. We collected and integrated interdisciplinary datasets in order to assess the biophysical, agronomic, social and economic realities at the sites. The study was carried out in four CCAFS Benchmark sites in East Africa, representing various agro-ecological systems: Hoima, Uganda; Nyando, Kenya; Lushoto, Tanzania; and Borana, Ethiopia. The information is being used for researchers, policy-makers and development practitioners to better understand the vulnerabilities of smallholder farmers, both men and women, to climate ch ange and what actions can be taken to reduce that vulnerability.